Covariance components and genetic parameters in reproductive traits of Santa Gertrudis heifers - Morales, Y.; Hern?ndez, Arelis; Gonzales-Pe?a, Dianelys; Cos, Yusel C.; Rodr?guez, M. (Cuban Journal of Agricultural Science, 2013)
Variance components and genetic parameters of the reproductive traits age at incorporation (AI), age at first service (AFS), age at first calving (AFC) weight at incorporation (WI) and weight for age (WFA) were estimated in 5896 Santa Gertrudis heifers born between 1975 and 2006 in the Cuban cattle breeding enterprises ?Rancho Vallina?, Turiguan?? and ?Camilo Cienfuegos?. An animal multi-trait model was used in which as fixed effect was considered the contemporary group, including the combination enterprise-year-birth season and as random the animal and the residual effect. The pedigree file comprised 11 966 animals, from 176 bulls and 3 448 dams. The highest heritability estimates were obtained for AI (0.16) and for WI (0.15). However, the lowest value was for AFC (0.07). The genetic correlations were significant with the highest estimate for AFS and AFC (0.99); while the AI and WFA (-0.86) showed a strong and negative correlation. The environment greatly influenced on all traits. The genetic correlations between traits demonstrated the improvement possibility through WFA which could be an important selection criterion for Santa Gertrudis heifers. Key words: heritability, genetic correlations, AI incorporation, Santa Gertrudis